Students’ Argumentation through Mathematical Literacy Problems Based on Mathematical Abilities - Yaffi Tiara Trymelynda; Rooselyna Ekawati (Program Studi S1 Matematika UNESA, 2023)
Argumentation is an essential mathematical skill employed in mathematical literacy. Argumentation is an individual's ability to think critically to provide reasons based on facts to make conclusions that solve problems. A qualitative approach is used in this study to describe students' argumentation in solving mathematical literacy problems based on mathematics ability level. The research subjects were three twelfth-grade students: one with high mathematics ability, one with moderate mathematics ability, and one with low mathematics ability, which was selected purposively. Data are collected through mathematical literacy problem tests and interviews. The data are analyzed using McNeill and Krajcik's argumentation components: claim, evidence, reasoning, and rebuttal in solving mathematical literacy problems. The results showed that students with high mathematical abilities could formulate and perform the procedures at the evidence indicator; connect information for reasoning indicators; provide general solutions, represent and assess the mathematical solutions at the rebuttal indicators; and make a correct claim. Students with moderate mathematical ability could apply mathematical concepts although made a miscalculation at the evidence indicator; connect information for reasoning indicators; provide partially correct solutions; represent and evaluate the sufficiency of the mathematics solutions at the rebuttal indicator; and make a correct claim. Meanwhile, students with low mathematical ability miss a crucial concept and make miscalculations at the evidence indicator; connect information for reasoning indicators; provide and represent partially correct solutions but cannot evaluate the sufficiency of the mathematics solutions at the rebuttal indicator; provide a correct claim. Keywords: Argumentation, McNeill Argumentation, Mathematical Literacy Problems, Mathematical Abilities.